ISCHEMIC HEART DISEASE AND RENAL DYSFUNCTION - F. I. Belyalov (Столичная издательская компания, 2017)
The ischemic heart disease (IHD) with comorbid kidney dysfunction has more severe course and worse prognosis, regardless of the chosen therapeutic strategy for the treatment of coronary disease. Traits of diagnosis and treatment of IHD in patients with renal dysfunction, including end-stage kidney disease, are discussed. The analysis of the studies showed increasing difficulties in the diagnosis of IHD, and decrease in the effectiveness of drug and invasive treatment.Results of large randomized and observational studies can help to treat patients with IHD and comorbid renal dysfunction more effectively and safe.